2014
DOI: 10.1021/jf405612a
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry Ellagitannins Thwarted the Positive Effects of Dietary Fructooligosaccharides in Rat Cecum

Abstract: Forty-eight male Wistar rats were fed diets containing low (0.051% of diet) or high (0.153% of diet) levels of an ellagitannin-rich (ET) strawberry extract with dietary fructooligosaccharides (FOS) or cellulose (CEL) for 4 weeks. The in vivo study demonstrated that some positive changes in the cecal metabolism resulting from the ingestion of a diet enriched only with FOS were completely or slightly suppressed by the dietary ET. In particular, the pH value (7.21 vs 7.36), short-chain fatty acid production (41.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 47 publications
(135 reference statements)
8
47
0
Order By: Relevance
“…As a result, the amount of substrates used in fermentation processes (oligosaccharides and non-starch polysaccharides) may be similar in SBM-based and SBM-FB-based diets. In accordance with previous findings (Fotschki et al, 2014), we assumed that a decrease in the tannin content of FB seeds would limit the inhibitory effect of those compounds on the metabolic activity of gut microbiota. The substitution of LT for HT seeds led to an increase in the total concentration of SCFAs in the caecal digesta, but the total SCFA pool did not increase because the amount of digesta was smaller.…”
Section: Discussionsupporting
confidence: 85%
“…As a result, the amount of substrates used in fermentation processes (oligosaccharides and non-starch polysaccharides) may be similar in SBM-based and SBM-FB-based diets. In accordance with previous findings (Fotschki et al, 2014), we assumed that a decrease in the tannin content of FB seeds would limit the inhibitory effect of those compounds on the metabolic activity of gut microbiota. The substitution of LT for HT seeds led to an increase in the total concentration of SCFAs in the caecal digesta, but the total SCFA pool did not increase because the amount of digesta was smaller.…”
Section: Discussionsupporting
confidence: 85%
“…Both, in rats perfused with the fl uid containing glucose and in those treated with sucrose-containing fl uid, no metabolites in the blood serum have been found. This confi rmed earlier fi ndings that due to a large molecular size of ET, these compounds are not absorbed in the upper intestine but reach the large gut where ET are metabolized by microbiota [Fotschki et al, 2014]. Glucose, as a very hydrophilic monosaccharide, cannot cross biological membranes unaided, and it is absorbed and then taken to the tissues by transporters, mainly GLUT2 and SGLT1 [Scheepers et al, 2004].…”
Section: Discussionsupporting
confidence: 83%
“…They are characterized by a complex structure that has not been entirely explored. In general and due to their large molecular size, ET are not absorbed but reach the distal part of the gastrointestinal tract where they are metabolized by microbiota [Espin et al, 2007;Fotschki et al, 2014]. These results may indicate that ET could exert some biological effects in the gut while their metabolites (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Urolithin-A isolated from human urine by semipreparative HPLC was used as a standard for the quantification of ET metabolites. The detailed procedure of urolithin-A isolation is described elsewhere [15]. …”
Section: Methodsmentioning
confidence: 99%
“…A recent study performed in our laboratory suggested that dietary FOS can increase the content of nasutin-A, a metabolite of strawberry ETs, in the intestinal digesta of rats. Thus, some beneficial changes in the gut microbiota following simultaneous ingestion of those dietary components as well as a possible increase in ET bio-availability have been suggested [15]. …”
Section: Introductionmentioning
confidence: 99%